Transparency, Photography, and the A-Theory of Time - Tee, Sim-Hui (Problemos, 2018)
[full article, abstract in English; only abstract in Lithuanian]Walton’s thesis of transparency of photographs has spurred much dispute among critics. One of the popular objections is spatial agnosticism, an argument that concerns the inertia of egocentric spatial information vis-a-vis a photograph. In this paper, I argue that spatial agnosticism fails. Spatial agnostics claim, for a wrong reason, that a photographic image cannot carry egocentric spatial information. I argue that it is the disjuncture of the photographic world in which the depicted object situated from the space in which the viewer of the photograph resides that renders the photograph spatially agnostic. It is the timeless photographic world rather than the photographic object that renders egocentric spatial information inert. With this new formulation of spatial agnosticism, I propose that spatial agnosticism needs to be coupled with the temporal dimension (the A-theory of time) in the efforts to refute the thesis of transparency of photographs.
Keywords: spatial agnosticism, the A-theory of time, transparency of photography, philosophy of arts, spatial information